2020
DOI: 10.1111/jfpp.15051
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐emulsioned linseed oil as animal fat replacement in sheep meat sausages: Microstructure and physicochemical properties

Abstract: The objective of this research was to investigate the inclusion of pre‐emulsified linseed oil as animal fat replacement on physicochemical properties and microstructure of sheep sausage. Control (0%) and formulations with 10, 20, 30, and 40% pre‐emulsified linseed oil were elaborated. Chemical composition was affected by the partial replacement of animal fat by linseed oil, since the sausages prepared with 40% linseed oil showed the highest protein and ash content. In addition, these sausages presented the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Soy protein is commercially available as soy protein isolates or concentrates and widely used in food products due to an excellent nutritional value with desired functions as a gelling agent. Many studies (de Souza Paglarini, de Figueiredo Furtado, Honório, et al., 2019; Utama et al., 2019; Lima et al., 2021; Wirkowska‐Wojdyła et al., 2021) used soy protein in emulsion formulations, which led to an improved gel network and enhanced cooking yield of the final products. Carrageenan is an algal‐based polysaccharide that affects the syneresis and hardness of emulsions.…”
Section: Methods To Incorporate Plant‐based Oils In Processed Meat Pr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Soy protein is commercially available as soy protein isolates or concentrates and widely used in food products due to an excellent nutritional value with desired functions as a gelling agent. Many studies (de Souza Paglarini, de Figueiredo Furtado, Honório, et al., 2019; Utama et al., 2019; Lima et al., 2021; Wirkowska‐Wojdyła et al., 2021) used soy protein in emulsion formulations, which led to an improved gel network and enhanced cooking yield of the final products. Carrageenan is an algal‐based polysaccharide that affects the syneresis and hardness of emulsions.…”
Section: Methods To Incorporate Plant‐based Oils In Processed Meat Pr...mentioning
confidence: 99%
“…Besides enhancing fatty acid composition, hydrogelled emulsions also improved cooking yield, oxidative stability, and sensory properties (few exceptions of full fat replacements) of the reformulated products. Recently, various studies (dos Santos et al., 2020; Lima et al., 2021; Pintado & Cofrades, 2020; Pereira et al., 2020; Kim et al., 2020; de Carvalho, Munekata, de Oliveira, et al., 2020; Shin et al., 2020; Vargas‐Ramella, Munekata, et al., 2020; Kim et al., 2021; Câmara et al., 2021; de Souto et al., 2021; Pintado et al., 2021; Bellucci et al., 2021; Öztürk‐Kerimoğlu, Kavuşan, et al., 2021; Kumar et al., 2021; Zhu et al., 2021) discussed the successful improvement in the nutritional profile of processed meat products (i.e., bologna sausages, frankfurters, fresh sausages, fermented sausages, betters, pâté) using hydrogel emulsions to replace animal fat with different plant‐based oils. However, few studies showed negative impact on textural parameters, especially because of full fat replacements.…”
Section: Methods To Incorporate Plant‐based Oils In Processed Meat Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…The modified sausages have a high protein content, low lipid value, high water retention capacity, and better emulsion stability, technological characteristics desired for this type of product, both by the consumer and the food industry (Garcia-Santos et al, 2019). The lipid reformulation process did not affect oxidation rates, indicating that sheep sausage can be produced with pre-emulsified linseed oil up to a concentration of 40% without this process causing any deleterious effects on the physicochemical aspect and the quality of the final product (Lima et al, 2021). In this context, aspects related to the changes in these products during the storage period are of great interest for investigating quality.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-emulsified linseed oil to replace animal fat in sheep meat sausages promoted specific characteristics for emulsion systems in the microstructure, resulting in more compact and firm sausages (Lima et al, 2021). The modified sausages have a high protein content, low lipid value, high water retention capacity, and better emulsion stability, technological characteristics desired for this type of product, both by the consumer and the food industry (Garcia-Santos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%